Pola Asuh Orangtua Over Protective terhadap Perkembangan Sosial Anak di Tk Islam Khaira Ummah Ikur Koto Kec. Koto Tangah kota Padang - Febiola, Fifi; Izzati, Izzati (Jurnal Caksana : Pendidikan Anak Usia Dini, 2019)
Abstract This study aims to describe the symptoms of over protective foster behsvior towards the social development of children in islamic kindergartens khaira ummah ikur koto kec. Koto tangah padang city. This study uses a qualitative approach with descriptive study methods.The researcher uses parents and teachers as informants. How to use the date used by researchers is observasi, interviews, and documentation.Based one the descriptive and data analysis, it can be concluded that the research shows that parents provide parenting patterns that tend to be over protective of their children. This is indicated by the form of protective provided by parents to their children, and does not provide an opportunity for children to be able to do it themselves. The over protective parenting has an impact on children’s social development, namely children are difficult to adapt to the new environment, prefer to play alone, and result in children not being independent.